Comparative study between open versus laparoscopic inguinal hernioplasty - A. P., Manjunath; K. N., Rajesh; H. R., Pallavi; Jayaram, V. Harsha (International Journal of Research in Medical Sciences, 2024)
Background: Inguinal hernia repair is one of the commonly performed procedure and has undergone a paradigm shift from open to laparoscopic approach in the era of minimally invasive surgery but the superiority is still debatable. The aim was to compare open (Lichtenstein) versus laparoscopic transabdominal preperitoneal approach (TAPP) hernia repair techniques. Methods: A total of 60 patients were enrolled in the study and divided into two equal groups (open versus laparoscopic) were compared. Results: It was observed that laparoscopic repair (TAPP) has statistically significant superiority than open inguinal hernioplasty in terms of lesser post-operative pain (VAS score of 4.8±0.66, 3.67±0.66, 2.53±0.82 versus 6.7±0.92, 5.03±0.72, 3.83±0.65 at 24 hours, 48 hours and 72 hours post operatively, p value <0.001), shorter duration of hospital stay (3.1±0.71 days versus 5.83±0.75 days, p value <0.001) and early resumption to regular activities (10.57±2.28 days versus 12.2±1.52 days, p value 0.002). It also showed that incidence intra operative and post-operative complications was lesser in laparoscopic group but not statistically significant. Whereas duration of surgery was prolonged in laparoscopic group (104±27.49 min versus 61.5±17.08 min, p value <0.001). Conclusions: Laparoscopic inguinal hernioplasty (TAPP) is superior to open inguinal hernioplasty in terms of lesser intra operative and post-operative complications, lesser post-operative pain, shorter duration of hospital stay with early resumption to regular activities having better subjective and objective cosmetic results in short term follow-up. However, duration of surgery was prolonged on comparison with Lichtenstein open inguinal hernioplasty.